Determination of Autosomal Dominant or Recessive Methionine Adenosyltransferase I/III Deficiencies Based on Clinical and Molecular Studies - Yoo-Mi Kim; Ja Hye Kim; Jin-Ho Choi; Gu-Hwan Kim; Jae-Min Kim; Minji Kang; In-Hee Choi; Chong Kun Cheon; Young Bae Sohn; Marco Maccarana; Han-Wook Yoo; Beom Hee Lee (BMC, 2016)
Abstract Methionine adenosyltransferase (MAT) I/III deficiency can be Inherited as autosomal dominant (AD) or as recessive (AR) traits in which mono- or biallelic MAT1A mutations have been identified, respectively. Although most patients have benign clinical outcomes, some with the AR form have neurological deficits. Here we describe 16 Korean patients with MAT I/III deficiency from 15 unrelated families identified by newborn screening. Ten probands had the AD MAT I/III deficiency, while six had AR MAT I/III deficiency. Plasma methionine (145.7 µmol/L versus 733.2 µmol/L, P < 0.05) and homocysteine levels (12.3 µmol/L versus 18.6 µmol/L, P < 0.05) were lower in the AD type than in AR type. In addition to the only reported AD MAT1A mutation, p.Arg264His, we identified two novel AD mutations, p.Arg249Gln and p.Gly280Arg. In the AR type, four previously reported and two novel mutations, p.Arg163Trp and p.Tyr335*, were identified. No exonic deletions were found by quantitative genomic polymerase chain reaction (PCR). Three-dimensional structural prediction programs indicated that the AD-type mutations were located on the dimer interface or in the substrate binding site, hindering MAT I/III dimerization or substrate binding, respectively, whereas the AR mutations were distant from the interface or substrate binding site. These results indicate that the AD or AR MAT I/III deficiency is correlated with clinical findings, substrate levels and structural features of the mutant proteins, which is important for the neurological management and genetic counseling of the patients.